1998
DOI: 10.1001/archotol.124.3.278
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Tympanostomy Tubes Inserted for Facilitation of Hyperbaric Oxygen Therapy

Abstract: The rate of complications is higher than reported for placement of tympanostomy tubes in other patient populations. Coexisting illness, such as diabetes mellitus, may contribute to the development of complications in patients undergoing hyperbaric oxygen therapy. Alternative methods of tympanostomy, with emphasis on shorter duration of intubation, should be considered in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
1
6
0
4
Order By: Relevance
“…Middle ear complication have been reported frequently; patients who can autoinflate their middle ears suffer less barotrauma than those who cannot. It has been suggested that pressure equalization tubes be offered to patients with Eustachian tube dysfunction undergoing barotherapy [12,13], although otorrhea affects 29% and persistent tympanic membrane perforation affects seven percent of patients undergoing HBO therapy despite ventilator tube insertion [14].…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%
“…Middle ear complication have been reported frequently; patients who can autoinflate their middle ears suffer less barotrauma than those who cannot. It has been suggested that pressure equalization tubes be offered to patients with Eustachian tube dysfunction undergoing barotherapy [12,13], although otorrhea affects 29% and persistent tympanic membrane perforation affects seven percent of patients undergoing HBO therapy despite ventilator tube insertion [14].…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%
“…Kabin ile orta kulak basıncı arasındaki eşitsizlik dengelenemediğinden, orta kulak basınca maruz kalarak kulakta ağrı ve işitme kaybı oluşabilir. EOM yanında hiperbarik oksijen tedavisine bağlı olarak timpanik membran perforasyonları, kemik zincir dislokasyonları, oval ve yuvarlak pencere yırtıklarına bağlı vertigo ve sensorinöral işitme kaybı görülebilir (40). Hiperbarik oksijen tedavisi östaki mukozasında ödem ve disfonksiyona neden olurken nazal mukozada önemli fonksiyon kaybına neden olmamaktadır (41).…”
Section: Hiperbarik Oksijen Tedavisine Bağlı Barotravmaunclassified
“…Hiperbarik O 2 tedavi süresi ortalama dört hafta olup miringotomi ve VT uygulaması bu sürede gelişen barotravmada uygun olarak kullanılabilir (42). Hiperbarik oksijen tedavisi sonrası VT takılan hastalarda komplikasyonların daha çok görüldüğü ve diabetes mellitusun komplikasyonlar için predispozan faktör olduğunu bildirilmiştir (40). Hiperbarik oksijen tedavisinin VT'nün timpanik membranda kalma süresinden daha önce bitmesinden dolayı, hem VT tatbikinden daha kısa süreli etkili bir yöntem bulmak hem de otore gibi komplikasyonları azaltmak amacıyla; termal yöntemle miringotomi ve intravenöz kanülün modifiye edilerek kısa süreli tatbiki gibi yön-temler uygulayan yazarlar mevcuttur (39,43).…”
Section: Hiperbarik Oksijen Tedavisine Bağlı Barotravmaunclassified
“…La complication la plus communément connue est la myopie progressive réver-sible due à une déformation de la cornée. Les barotraumatismes des sinus et de l'oreille moyenne ont été décrits et peuvent être prévenus par les techniques d'égalisation de pression (14). Ces complications peuvent être préve-nues par des pauses au cours de la séance d'oxygéno-thérapie hyperbare (4).…”
Section: Observationunclassified